Child Survival Strategies: Assessment of Knowledge and Practice of Rural Women of Reproductive Age in Cross River State, Nigeria - Aniekan Jumbo Etokidem; Ofonime Johnson (Journal of Tropical Medicine)
Introduction. Nigeria is one of the five countries that account for about 50% of under-five mortality in the world. The objective of this study was to assess the knowledge and practice of child survival strategies among rural community caregivers in Cross River State of Nigeria. Materials and Methods. This descriptive cross-sectional survey used a pretested questionnaire to obtain information from 150 women of reproductive age. Data analysis was done using SPSS version 20. Results. The child survival strategy known to most of the respondents was oral rehydration therapy as indicated by 98% followed by female education by 73.3% and immunization by 67.3%. Only 20% of the respondents had adequate knowledge of frequency of weighing a child while only 32.7% knew that breastfeeding should be continued even if the child had diarrhea. More respondents with nonformal education (83.3%) practiced exclusive breastfeeding of their last children compared to respondents with primary education (77.3%), secondary education (74.2%), and tertiary education (72.2%). Conclusion. Although respondents demonstrated adequate knowledge and practice of most of the strategies, there was evidence of gaps, including myths and misconceptions that could mar efforts towards reducing child morbidity and mortality in the state.